A Code of Ethics for Social Marketing? Bridging Procedural Ethics and Ethics-in-Practice. Issue 1 (2nd January 2017) - Carter, Stacy M.; Mayes, Christopher; Eagle, Lynne; Dahl, Stephan
ABSTRACT: We consider the role of codes of ethics in social marketing, distinguishing between "procedural ethics" and "ethics-in-practice" (after Guillemin & Gillam, 2004). We review foundations for "procedural ethics"—formal systems for ethical oversight—including moral and political philosophy, existing codes of ethics, and previous proposals for codes of ethics for social marketing. We then discuss "ethics-in-practice, " the ethical dimensions of the small moments that comprise everyday life. We connect this idea to Aristotle's concept of phronesis, the practical wisdom to respond in just the right way to particular situations. Supporting the ethical practice of social marketing will require both procedural ethics and ethics-in-practice, iteratively related to one another. We conclude with three tasks for the profession: (1) develop and apply norms, standards, and sanctions; (2) develop formal, procedural ethics, in a just way (e.g., codes of ethics); and (3) support social marketers to develop ethics-in-practice, or phronesis.